Effect of Nursing Educational Program on Recovery Following CABG Surgery: Intervention Study - Al-gersha, Khalida; Haboubi, Ghalib; Al-Asady, Najih (Iraqi National Journal of Nursing Specialties, 2005)
This intervention study is composed on 55 patients at Saddam Center for Cardiac Surgery (Aben-Albetar) throughout the period from 1st of July 1997 to 15th of January 1999. The study aimed to evaluate the effectiveness of constructed nursing education program on reduction of complications and improving recovery among patients with Coronary Artery Bypass Graft (CABG) surgery through the application of repeated measures. The sample is divided into 27 patients who received the nursing educational program (study group) and 28 patients who continued to receive regular care (controls). Based on previous research methods, were followed-up for 3 months after surgery. .To evaluate the effectiveness of the intervention education program , two major instrument were used, these instrument included knowledge test and self-efficacy check list. The knowledge given to the patient in study group prior to the implementation of the intervention program and re-tested at discharge and on three months after the operation and in the control group given knowledge test pre operative and re-tested at discharge and on three months after the operation. Self efficacy check list it was assessed at time of discharge and at first, second, and third month after discharge for the study and control groups. (6, 12) The result revealed that marked improvement in health status of the study group compared to the control group. The patient’s recovery was determined by percentages of indices of self-efficiency, and knowledge level. The indices were found to be higher for patients who received nursing education program throughout the period of study. In light of these findings, the investigator recommends that the implementation of an educational program by nurses for patient with open heart surgery and reinforcement of education during the follow-up period concerning to the patients’ need.